PERLAKUAN AKUNTANSI UNTUK ASET BERSEJARAH (Studi Fenomenologi pada Pengelolaan Candi Borobudur) - Fauziah Galuh Anggraini; Anis Chariri (Diponegoro Journal of Accounting, 2014)
This study is the phenomenon of the accounting treatment applied to heritage assets in Indonesia, both in terms of recognition, valuation, and disclosure in the financial statements. The focus of this study is an analysis of the accounting treatment in the management of Borobudur. This study aimed to: understand the significance of historic assets (heritage assets), describes the methods used to assess the Borobudur temple, explaining Borobudur’s disclosure in the financial statements, and analyze the appropriateness of the accounting standards applicable to the accounting for current Borobudur. The results of this study indicate that there is no precise definition of heritage assets. This is evidenced by the exposure to most of the informants who always associate with the historic definition of asset definition Heritage so there is confusion between the two. In addition, the manager of Borobudur is still experiencing difficulties in assessing valuation on heritage assets . However , the practice of accounting in the management of Borobudur Temple is considered to be in accordance with the accounting standards set by the government , which is presented and disclosed in CaLK without value .